Invest Peru and the Capabilities of the Armed Forces for National Defense 2023 - Cano, Jerry (2023)
This article analyzes the performance of the National Multiannual Programming and Investment Management System Invierte.pe in the field of defense. The objective of the research was to determine the effectiveness of Invierte.pe in improving the military capabilities of the armed forces for national defense. A quantitative approach was used with the review of State budget allocations for capital expenditure. For this, the analysis of the MEF budget execution reports was used. It was found that there are differences in budget allocation by year, depending on the government in power, just as there are considerable differences in the allocation of resources and their execution in each institution of the armed forces. It was concluded that the effectiveness of Invierte.pe for national defense depends on the management of the institutions of the armed forces more than on the administrative system itself.